Implementing farmers' rights relating to seeds - Carlos María Correa (South Centre, 2017)
The concept of Farmers' Rights recognized the role of farmers as custodians of biodiversity and helped to draw attention to the need to preserve practices that are essential for sustainable agriculture. This paper examines one particular aspect of such rights, perhaps the most controversial. It deals with the component of farmers' rights referring to the use, exchange and sale of farm-saved seeds. Although that concept was initially introduced in 1989 with the aim of balancing the rights of farmers as breeders and of commercial plant breeders, a specific reference to the rights relating to seeds was only introduced upon the conclusion of the International Treaty on Plant Genetic Resources for Food and Agriculture (ITPGRFA) in 2001.
Keywords: 300; Saatgut; Gentechnisch verändertes Produkt; Artenvielfalt; Patentrecht; Landwirte; Pflanzenzüchtung; Außenwirtschaftsrecht; Welt